Deletion of autophagy inducer RB1CC1 results in degeneration of the retinal pigment epithelium - Yao, Jingyu (Autophagy, 2015)
Autophagy regulates cellular homeostasis and response to environmental stress. Within the retinal pigment epithelium (RPE) of the eye, the level of autophagy can change with both age and disease. The purpose of this study is to determine the relationship between reduced autophagy and age-related degeneration of the RPE. The gene encoding RB1CC1/FIP200 (RB1-inducible coiled-coil 1), a protein essential for induction of autophagy, was selectively knocked out in the RPE by crossing Best1-Cre mice with mice in which the Rb1cc1 gene was flanked with Lox-P sites (Rb1cc1(flox/flox)). Ex vivo and in vivo analyses, including western blot, immunohistochemistry, transmission electron microscopy, fundus photography, optical coherence tomography, fluorescein angiography, and electroretinography were performed to assess the structure and function of the retina as a function of age. Deletion of Rb1cc1 resulted in multiple autophagy defects within the RPE including decreased conversion of LC3-I to LC3-II, accumulation of autophagy-targeted precursors, and increased numbers of mitochondria. Age-dependent degeneration of the RPE occurred, with formation of atrophic patches, subretinal migration of activated microglial cells, subRPE deposition of inflammatory and oxidatively damaged proteins, subretinal drusenoid deposits, and occasional foci of choroidal neovascularization. There was secondary loss of photoreceptors overlying the degenerated RPE and reduction in the electroretinogram. These observations are consistent with a critical role of autophagy in the maintenance of normal homeostasis in the aging RPE, and indicate that disruption of autophagy leads to retinal phenotypes associated with age-related degeneration.